1995
DOI: 10.1021/jm00026a011
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of the Antimalarial Agent Artemisinin. 2. Effect of Heteroatom Substitution at O-11: Synthesis and Bioassay of N-Alkyl-11-aza-9-desmethylartemisinins

Abstract: A novel class of artemisinin analogs, N-alkyl-11-aza-9-desmethylartemisinins 17-29, were synthesized via ozonolysis and acid-catalyzed cyclization of precursor amides 5-16. These amides were prepared through condensation of an activated ester of the known intermediate acid 2 with the corresponding primary amine. The analogs were tested in vitro against W-2 and D-6 strains of Plasmodium falciparum and found in some cases to be more active than artemisinin. A comparison of the in vitro testing methods of Milhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…ART is a lipophilic molecule with a logP value of 2.65 ± 0.3. The toluene-water partition coefficient obtained in this experiment was in good agreement with the literature logP (octanol-water) value (2.90) [23] and clogP value (2.40). Tables 2-4 describe the solubility of ART in the presence of different concentrations of PVP in the three solvent systems examined in this work.…”
Section: Discussionsupporting
confidence: 90%
“…ART is a lipophilic molecule with a logP value of 2.65 ± 0.3. The toluene-water partition coefficient obtained in this experiment was in good agreement with the literature logP (octanol-water) value (2.90) [23] and clogP value (2.40). Tables 2-4 describe the solubility of ART in the presence of different concentrations of PVP in the three solvent systems examined in this work.…”
Section: Discussionsupporting
confidence: 90%
“…The group of Avery synthesized a number of aza-desmethylartemisinins 38, 17 as a late synthetic precursor 39 was readily available from their artemisinin total synthesis project (Scheme 12). 4 Carboxylic acid 39 was converted to the corresponding mixed anhydride with ethyl chloroformate.…”
Section: -Aza-9-desmethylartemisininsmentioning
confidence: 99%
“…We have already demonstrated that certain azaartemisinin derivatives possess greatly enhanced thermal stabilities 19 and several have good antimalarial activities. 17,20 We describe here the preparation of selected N-alkane-and arenesulfonyl-11azaartemisinins that are screened against asexual and sexual blood stages of P. falciparum. The antimalarial activities are compared with cytotoxicities of the azaartemisinins against a non-proliferating mammalian cell line.…”
Section: Introductionmentioning
confidence: 99%